THE PSYCHOSOCIAL IMPLICATIONS OF THE CLOSING OF A MINE FOR WORKERS AND THEIR FAMILIES - Strydom, Herman; Herbst, Alida (Social Work/Maatskaplike Werk, 2008)
This article arose from a project which was launched on behalf of the Labour Union Solidarity after the interim liquidation and immediate closing of the Durban Roodepoort Deep (DRD) Gold Mine at Stilfontein. This mining community was also traumatized by an earthquake shortly before the closing of the mine. The process commenced on 27 April 2005, when a contract was drawn up with Solidarity’s Helping Hand Fund to do a psychosocial situation analysis among the community. Based on the results of the psychosocial situation analysis, a project plan was submitted to Solidarity, after which a formal agreement was reached between the two parties and a meeting with the representatives of the labour union was held. Following this, the plan of action was proposed, the facilitators trained and the programme implemented. The data of the psychosocial situation analysis, the contents and course of the group sessions as well as the results that ensued from the questionnaire that was filled in by the women during the women’s day as well as certain strengths present in the community are discussed. This is followed by an integrated discussion of the investigation. A number of recommendations are also made for the future.